Screening for oral language alteration in children referred to a hearing health service (Research, Society and Development, 2022)
Audiological evaluation is indicated for differential diagnosis purposes in relation to non-linguistic development delays, language development disorders, two-child speech disorders, autism spectrum disorders (ASD), neurological and genetic disorders and/or metabolic. Objective: To track oral language problems in children referred to a hearing health service. Method: 22 clinical videos recorded of subjects aged 2.0 to 4.0 years, 19 males and 03 females, validated in a hearing health service.  The screening instrument “How does your child hear and speak?” was used to pigtail two dice. Two results were analyzed: a descriptive analysis was performed on two data using absolute and relative frequencies. Association analysis was performed using Fisher´s exact test. The median age was 3.1 years. Most children (86,4%) had no hearing loss. Regarding language problems, 77.2% were unable to perform the screening, presenting difficulties in both expressive language (81.8%) and receptive language (72.7%). The subjects with hearing loss (11.8%) had greater difficulties in the receptive aspects (11.8%), and the subjects didn’t achieve expressive language (88.9%). I found that there was no statistically significant association between hearing loss and receptive language variations. Conclusion: The significant number of subjects with evidence of language disorders found in the studied sample deserves attention. The data presented point out the importance of referral for the differential diagnosis of possible language disorders in hearing health services, thus contributing to early intervention.